CARDIOVASCULAR SCREENING IN ASYMPTOMATIC TYPE 1 DIABETES PATIENTS: PRELIMINARY RESULTS AND MODEL PROPOSAL FOR A COST-EFFECTIVENESS ANALYSIS. (April 2021) - Helleputte, Simon; Lapauw, Bruno; Calders, Patrick; De Backer, Tine
Abstract: Objective: Background: Type 1 diabetes (T1DM) is an independent risk factor for cardiovascular disease (CVD), with patients being considered as a high or even very high risk group. However, routine screening for CVD in an asymptomatic T1DM population is currently not recommended. Moreover, the cost-effectiveness of such screening programs has been subject of debate. Objectives: Discuss results and perform a cost-effectiveness (CEA) and cost-utility (CUA) analysis of a CVD screening program (2013–2019) in a Belgian cohort of asymptomatic T1DM patients. Setting: Ghent University Hospital (Flanders, Belgium). Methods: Adult T1DM patients with a minimum disease duration (DD) of 10 years and without known macrovascular disease were enrolled in a CVD screening program, including: coronary artery calcium (CAC) scoring, cyclo-ergometry, transthoracic echocardiography, 24-hour Holter monitoring, and carotid ultrasound. A decision-analytic Markov model is applied to compare estimated costs and health outcomes (i.e. CVD events and quality-adjusted life years or QALYs) of the screening program vs. usual care (i.e. no screening). After screening, patients were categorised in five possible Markov states: (1) "No additionally increased risk" in case of no significant abnormalities being detected; (2) "Soft attention" in case of mild to moderate alterations or doubtful findings; (3) "Hard attention" if CAC > P90 or absolute > 400 Agatston score, i.e. subclinical high atherosclerotic burden; (4) "Unequivocally documented CVD on imaging" if presence of significant carotid plaque; and (5) "Documented clinical CVD" if patients were referred for coronary revascularization. The Markov model further includes stroke, myocardial infarction (MI) and death. Time horizon of the model is 10 years and a healthcare payer perspective will be applied. Results of the CEA will be expressed in incremental costs per event avoided (stroke and MI), and the CUA in incremental costs per QALY gained. Both one-way and probabilistic sensitivity analyses will be performed. To report on CUA, a willingness-to-pay threshold of [Euro sign]40 000 per QALY will be applied. Preliminary results: 97 patients (M/F: 61/36; age: 45 ± 10.0 years; DD: 24 ± 10.1 years; HbAc1: 7.7 ± 0.75%, BMI: 25 ± 3.0 kg/m2) were included. The CVD screening program yielded the following results: (1) "No additionally increased risk after screening": n = 68/97 (70.1%); (2) "Soft attention": n = 16/97 (16.5%); (3) "Hard attention": n = 8/97 (8.2%); (4) "Unequivocally documented CVD on imaging": n = 2/97 (2.1%); and (5) "Documented clinical CVD": n = 3/97 (3.1%). Up to now, one event (MI) has occurred during follow-up (being a patient from group 1).